A Prospective Study of Management of Proximal Humerus Fractures with LCP Plate - V. Venugopal; P. Sukarna Reddy (Asian Journal of Medical Research, 2017)
Introduction: Proximal Humerus fractures account for 4% of all fractures. Most proximal humerus fractures can be managed conservatively, but 3-part and 4-part fractures are unstable and need internal fixation. We are undertaking this study to get a better understanding of the use of operative management of these fractures with LCP plating.Methods: A retrospective study of 50 cases (32 males, 18 females) with unstable fractures of proximal humerus treated from June 2013 to Dec 2016 in the mean age 51.5 (25-70) years formed the study group. Indications for surgery were 3-part & 4-part closed proximal humeral fractures, surgical neck fractures with angulation greater than 45 degrees or greater tuberosity fracture with displacement of more than 1 cm.Results: Excellent to satisfactory results were seen in 80% of cases. The poor outcome was due to gross osteoporosis and comminution. Conclusion: Locking Compression plate is an advantageous implant in proximal humeral fractures due to angular stability, particularly in comminuted fractures and in Osteoporotic bones in elderly patients, thus allowing early mobilization. Keywords: proximal humerus fracture, locking plate, mal union.